Fiscal Monitor, April 2011 : Shifting Gears. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2011)
With increasing fiscal challenges in the aftermath of the global financial crisis, multilateral surveillance of fiscal developments, a key part of the IMF's surveillance responsibilities, has gained further importance. In response, the Fiscal Monitor was launched in 2009 to survey and analyze the latest public finance developments, update fiscal implications of the crisis and medium-term fiscal projections, and assess policies to put public finances on a sustainable footing. The Fiscal Monitor is prepared twice a year by the IMF's Fiscal Affairs Department. Its projections are based on the same database used for the IMF's World Economic Outlook (WEO) and Global Financial Stability Report (GFSR).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet